Functionalization of pyridines and pyrimidines via ring-opened intermediates - Uhlenbruck, Benjamin J. H., author; McNally, Andrew, advisor; Miyake, Garret, committee member; Chung, Jean, committee member; Kipper, Matt, committee member (Colorado State University. Libraries, 2025)
Pyridines and pyrimidines are prevalent in pharmaceuticals and agrochemicals, yet site-selective functionalization methods of these valuable structures are often limited. In this dissertation, we describe the development of pyridine and pyrimidine functionalization methods that will enable organic chemists to access functionalized heterocyclic materials more easily. Chapter One describes the importance of pyridines and pyrimidines in industry, along with current methods and limitations in functionalizing these azines. Chapter Two introduces a 3-selective chlorination of pyridines using ring-opened Zincke imine intermediates. The method differs from a method our group reported in 2022 by ring-opening pyridine with aniline instead of dibenzylamine. Ring-opening azines with aniline produces imines and N-Ph azine salts with interesting properties, and enables the transformations described in every chapter of this dissertation. Chapter Three describes a 3-selective fluorination of pyridines using Zincke imine intermediates. Chapter Four provides an overview of Structure-Activity-Relationship (SAR) studies, de novo heterocycle synthesis, and skeletal editing strategies, then describes a deconstruction-reconstruction approach for pyrimidine diversification. Chapter Five discusses stable isotopes in medicinal chemistry, then expands on the deconstruction-reconstruction strategy for stable isotope incorporation into pyrimidines.
Keywords: heterocycle; organic chemistry; C-H functionalization; skeletal editing; late-stage functionalization